O PAPEL DAS FERRAMENTAS DE GESTÃO DO CONHECIMENTO NA PERFORMANCE DE UM SISTEMA DE BIBLIOTECAS ACADÊMICAS: UM DIAGNÓSTICO A PARTIR DO CASO CEFET/RJ - Oliveira, Luciana Carvalho de (2013)
Knowledge management is a new management vision for organizations today, since information and knowledge have become key factors in competitiveness between individuals, organizations and nations. Thus, universities have in their libraries a way to generate efficacy because they are propitious spaces to the construction and dissemination of important scientific information. Thus, this study seeks to analyze and discuss the issue of knowledge management in the libraries system of a higher education institution. Describes the importance of this kind of management as a mechanism for improving organizational performance, highlighting the organizational sensemaking with essential integral part of this process. It features the communities of practice as knowledge management tools that promote organizational sensemaking. As for the research method, was adopted the case study, leaving the scope of work limited for the institution in question , the results may serve as paradigms for similar institutions. Was used the sequential mixed methods approach, consisting of two phases: quantitative and qualitative, with the objective of deepen the results. The results indicate the need for improving the organizational environment of the Libraries System, in order to make it more propitious to organizational knowledge management and therefore a source of competitive advantage to the institution in which it is inserted.